Reconstruction of Dakwah Verses - Rasidin, Mhd.; Witro, Doli; Purwaningsih, Rahma Fitria (UIN Sayyid Ali Rahmatullah Tulungagung, 2020)
Abstract Da’wah is an activity of inviting others to strengthen the faith of Muslims. The Prophet Muhammad has given examples of how Dakwah should be done. People who accept the materials of Dakwah depend on the way of ulama’s deliver the messages. Then, ulama’ will encounter problems whether people accept or reject what they said. The adherents of radicalism in Islam believe that the teaching of Islam should be presented in many ways, including coercion and violence. This understanding is based on how they interpret some verses in the Quran about dakwah. This paper will try to reconstruct some verses and how the dakwah should be conducted inclusively by describing the ethics of dawah. So, the image of dakwah is not only about the propagation of the Islamic Religion to convert non-muslim to Islam, but also strengthening and deepening the faith of Muslims and helping them lead their daily lives in conformity with Islamic principles. Keywords: Da’wah, Radicalism, Al-Qur’an. Abstrak Dakwah adalah aktivitas untuk mengundang orang lain dalam upaya menguatkan keimanan. Nabi Muhammad telah memberikan contoh bagaimana seharusnya dakwah dilakukan. Masyarakat menerima dakwah tergantung pada bagaimana ulama menyampaikan pesan-pesannya. Dimana kemudian, seringkali para ulama tersebut menghadapi berbagai persoalan apakah pesan tersebut diterima atau justru ditolak oleh masyarakat. Pada titik ini, para penganut radikalisme percaya bahwa ajaran Islam harus disampaikan secara tegas, bahkan jika harus dengan pemaksaan dan kekerasan. Pemahaman ini hadir berdasarkan pemahaman mereka terhadap ayat-ayat AlQuran. Artikel ini berupaya untuk merekonstruksi beberapa ayat AlQuran tentang bagaimana dakwah seharusnya dilakukan secara inklusif, dengan menjelaskan etika dakwah. Sehingga, gambaran tentang dakwah tidak hanya propaganda agama agar non muslim masuk islam, tetapi lebih pada penguatan dan pendalaman keimanan dan membantu masyarakat dalam memahami prinsip-prinsip keagamaan. Kata Kunci: Dakwah, Radikalisme, Al-Qur’an.